Effect of high plant density on growth and production variables of European pear cultivars and quince rootstock combinations in southern Brazil - Machado B.D.* (2014)
Pear culture has great potential for development in southern Brazil due to the climatic and soil conditions, and a favourable market. However, a lack of information about the best combinations between European pear cultivars and rootstocks as adapted to conditions in this area has limited the culture development. The aim of this study was to determine the effect of high plant density on vegetative and production variables such as growth, development and fruit production, of different combinations of European pear cultivars and quince rootstocks. The experiments were conducted in a commercial orchard under the edaphoclimatic conditions of the upland region of southern Brazil (1,425 m above sea level), during the growth seasons of 2008/09, 2009/10 and 2010/11. The cultivars evaluated were 'Santa Maria', 'Rocha', 'Abbé Fetel' and 'Packham's Triumph'. The quince rootstocks evaluated were EMC and Adams. The plant density was 7,500 trees ha-1, with a spacing of 0.3 m between trees and 4 m between rows. 'Abbé Fetel' grafted on Adams had the largest canopy volume and rootstock diameter, the lowest productivity with an estimated yield of 0.035 t ha-1, and a production efficiency of 0.01 kg m-3. 'Santa Maria' grafted on Adams had the smallest canopy volume and rootstock diameter, the highest productivity with an estimated yield of 19.7 t ha-1, and a production efficiency of 2.06 kg m-3.